PENGARUH VARIABEL MONETER DAN NON MONETER TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Thesya Yulianca; Sri Ulfa Sentosa; Selli Nelonda (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2017)
This study aims to determine and analyze the influence between monetary variables consisting of foreign investment and inflation on economic growth, and the influence of non-monetary variables consisting of total labor force and economic growth. The type of this research is descriptive research, where the data used is the time series data from 1984 to 2015 obtained from the World Bank and Central Bureau of Statistics (BPS) website, which is analyzed by Ordinary Least Square (OLS) method. The results of this study indicate that the monetary variables of foreign investment have a positive and significant impact on economic growth in Indonesia and inflation has a negative and significant effect on economic growth in Indonesia, while the non-monetary variable is the total labor force has an insignificant and positive effect on economic growth in Indonesia and Government spending has a significant and positive impact on economic growth in Indonesia.